A new record of hypodontia in Phyllostomus discolor with notes on its evolutionary implications - Juárez, Valentino; Ramos Pereira, Maria João; Aya-Cuero, Carlos; Esquivel, Diego A. (Therya Notes, 2026)
Dental anomalies are disruptions in the normal development of teeth, primarily caused by genetic mutations, leading to variations in the number, shape, size, eruption, and formation of hard tissues. Although these abnormalities have been observed in various mammalian groups, their incidence and implications remain underexplored. We identified one specimen of Phyllostomus discolor with a dental anomaly. Following this discovery, we made a review of dental anomalies in Chiroptera searching for specific terms related to bats and dental anomalies and then conducted a linear regression to detect the trend of publications. Here, we report a new record of hypodontia in the Pale Spear-nosed bat Phyllostomus discolor. The hypodontia was identified in a male specimen of the Pale Spear-nosed bat from the Andean region of Colombia, characterized by a missing incisor adjacent to internal incisors in the mandible, resulting in three lower incisors—one fewer than normal. Understanding the patterns, incidence, and variations of dental anomalies across mammalian clades can enhance taxonomic studies and elucidate the mechanisms driving dental trait diversification. However, we highlight a low interest in publications barely averaging 0.73 reports per year. Contrary to what was expected, and unlike other genetic, eco-devo and evolutionary approaches used to investigate mammalian teeth, we evidence a clear reduction and possible lack of interest in this topic. We urge researchers and curators to document such anomalies that allow to challenge current hypotheses about their occurrence and evolutionary implications.